2014
DOI: 10.1515/helia-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation Genetic Differentiation Orobanche cumana Wallr. from Russia, Kazakhstan and Romania Using Molecular Genetic Markers

Abstract: Broomrape (Orobanche cumana Wallr.) is an obligate parasite of higher plants, which affects sunflower in many countries, cultivating this crop. For the past decades, it is noted the formation of new highly virulent biotypes of broomrape and their spreading to other areas. In our work we studied the molecular genetic diversity of broomrape populations of O.cumana, parasitizing on sunflower in Russia, Romania, and Kazakhstan, by using codominant microsatellite markers. During cluster analysis, the broomrape popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 9 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Pineda-Martos et al (2013) detected 19 alleles (2 to 3 alleles/locus) for the same SSR loci as in our study. In the work of Guchetl et al (2014aGuchetl et al ( , 2014b, 17 alleles (2 to 4 alleles per locus) were detected for the same SSR loci, except Ocum-160, with our study. The results of band sizes and allele numbers of SSRs in various studies conducted with different O. cumana populations in the literature and in this study are consistent with each other.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Pineda-Martos et al (2013) detected 19 alleles (2 to 3 alleles/locus) for the same SSR loci as in our study. In the work of Guchetl et al (2014aGuchetl et al ( , 2014b, 17 alleles (2 to 4 alleles per locus) were detected for the same SSR loci, except Ocum-160, with our study. The results of band sizes and allele numbers of SSRs in various studies conducted with different O. cumana populations in the literature and in this study are consistent with each other.…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that the analyzed SSR loci have a significant level of heterozygote deficiency, and the main reasons for this are a higher fixation index and selfing rate value. Guchetl et al (2014aGuchetl et al ( , 2014b indicated higher heterozygosity in populations from Russia and Kazakhstan than populations from Romania. It is emphasized that geographic distance, different soil types, and climatic conditions might affect the level of heterozygosity in these populations.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations